Perancangan dan Pembuatan Sistem Penyalaan Lampu Otomatis Dalam Ruangan Berbasis Arduino Menggunakan Sensor Gerak dan Sensor Cahaya - Imam Marzuki (FT- UNDAR, 2019)
The manual use of household lights poses a problem in the efficiency of electricity use. Humans with various activities often do not pay attention to the condition of the lights in the room whether it lights up or not. This is certainly a waste of electricity when they leave the room without turning off the switch. Therefore, researchers propose an automation system that can save electricity from lighting. In designing the system there are two sensors used, namely Passive Infra Red (PIR) sensor and Light Dependent Resistror (LDR) sensor. PIR functions to detect the presence of human movements (objects) in the sensor work area, while the LDR sensor functions to detect the intensity of light around the room. The results of the system testing are that the PIR sensor works well around ± 2 minutes after the device is activated and the LDR Sensor will continuously measure the value of light intensity then turn on and off the light according to the programmed